Strategic Outsourcing Revisited - Stefan Buehler; Justus Haucap (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
This paper analyzes a sequential game where firms decide about outsourcing the production of a non-specific input good to an imperfectly competitive input market. We apply the taxonomy of business strategies introduced by Fudenberg and Tirole (1984) to characterize the different equilibria. We find that outsourcing generally softens competition in the final product market. If firms anticipate the impact of their outsourcing decisions on input prices, there may be equilibria where firms outsource so as to collude or to raise rivals' costs. We illustrate our analysis using a linear Cournot model.
urn:nbn:de:gbv:705-opus-1486
Keywords: D43; L24; L23; L22; 330; Outsourcing; Duopol; Unvollkommener Wettbewerb; Spieltheorie; Theorie